Production of oxidative and hydrolytic enzymes from Pleurotus florida and their implication in mushroom cultivation - KAUR, MANMEET; SHARMA, SHIVANI; KAUR, RAVNEET; SODHI, HARPREET SINGH (The Indian Journal of Agricultural Sciences, 2023)
One of the most economically viable processes for the bioconversion of many types of lignocellulosic wastes is represented by edible mushroom cultivation. Pleurotus florida is one of the prominent economically cultivated mushrooms with varied abilities to utilize lignocellulose as a growth substrate. Thus, the profile of oxidative and hydrolytic enzymes was measured during the submerged and solid-state fermentation at Punjab Agricultural University, Ludhiana, Punjab during the winter (rabi) season of the year 2020–21. The intracellular activity of laccase (10.23 IU/mg), manganese peroxidase (9.98 IU/mg), cellobiohydrolase (5.46 IU/mg) was best obtained in P. florida on the 14th day. The extracellular activity of laccase (15.43 IU/ml), lignin peroxidase (11.21 IU/ml), endoxylanases (9.22 IU/ml) were found to be highest on the 14th day. P. florida had substantial levels of ligninolytic enzymes during substrate colonization but rapidly diminished during fruit body development. On the other hand, P. florida showed relatively low hydrolase activity during substrate colonization. The activity of these enzymes increased when primordia formed. The hydrolytic activities peaked at the mature fruiting body stage. When mushrooms switched to vegetative development, ligninolytic enzyme activity increased again, while hydrolase activity declined. The yield was found to be 58.78% after the enzymatic treatment of paddy straw. These findings suggest that fluctuations in oxidative and hydrolytic enzyme activities are linked to the growth of the fruiting body and the physiological state of mushroom cultivation.